SISTEM SAPAAN BAHASA MELAYU DI SUNGAI RAYA KABUPATEN BENGKAYANG - Rizky, Dina; Sulissusiawan, Ahadi; Muzammil, Ahmad Rabiul (Universitas Tanjungpura, 2024)
The problem of this research is the Melayu language greeting system in Sungai Raya, Bengkayang Regency based on the form of greeting words, various greeting words and types of greeting words. The purpose of the study in general is to describe the Melayu greeting system in Sungai Raya, Bengkayang Regency. Its specific purpose is to describe the form of greeting words, various greeting words and types of Melayu greeting words in Sungai Raya, Bengkayang Regency. The method used in this study is the descriptive method. This form of research is qualitative. The collection of research data was carried out using questionnaire techniques, interview techniques and record techniques. The source of data in this study is native Melayu speakers in Sungai Raya, Bengkayang Regency and research data, namely words that contain greetings to the Melayu community in Sungai Pangkalan I Village, Bengkayang Regency. Based on research data, it was concluded that the form of the Melayu greeting word in Sungai Raya, Bengkayang Regency was determined based on position, gender, age, family, speech situation and order of birth. The kinds of Melayu greeting words in Sungai Raya, Bengkayang Regency, are determined based on greetings in the family, greetings in the community, official greetings, greetings in religion, greetings for guests, and greetings in written language. The type of Melayu greeting word in Sungai Raya, Bengkayang Regency, is determined based on noun greeting, adjective greeting, pronoun greeting and pungut word greeting.